Asymmetric synthesis of host-directed inhibitors of myxoviruses - Moore, Terry W.; Sana, Kasinath; Yan, Dan; Thepchatri, Pahk; Ndungu, John M.; Saindane, Manohar T.; Lockwood, Mark A.; Natchus, Michael G.; Liotta, Dennis C.; Plemper, Richard K.; Snyder, James P.; Sun, Aiming (Beilstein Journal of Organic Chemistry, 2013)
High-throughput screening (HTS) previously identified benzimidazole 1 (JMN3-003) as a compound with broad antiviral activity against different influenza viruses and paramyxovirus strains. In pursuit of a lead compound from this series for development, we sought to increase both the potency and the aqueous solubility of 1. Lead optimization has achieved compounds with potent antiviral activity against a panel of myxovirus family members (EC50 values in the low nanomolar range) and much improved aqueous solubilities relative to that of 1. Additionally, we have devised a robust synthetic strategy for preparing 1 and congeners in an enantio-enriched fashion, which has allowed us to demonstrate that the (S)-enantiomers are generally 7- to 110-fold more potent than the corresponding (R)-isomers.
Keywords: asymmetric synthesis; benzimidazole; host-directed; myxovirus; small molecule inhibitor